LARGE V PATTERN EXOTROPIA WITH BILATERAL INFERIOR OBLIQUE OVERACTION AND ITS CHALLENGING MANAGEMENT: Poster Presentation - Case Report - Resident - Rahmah Kartika, Amelia; Prastyani, Reni (Majalah Oftalmologi Indonesia, 2023)
Introduction : V pattern exotropia is a strabismus pattern with greater divergence in upgaze than downgaze. Various surgical treatment options were defined. This report demonstrates the management of largeV pattern exotropia with bilateral inferior oblique overaction (IOOA) by performing multiple surgeries. Case Illustration : A 20-year-old male came with a chief complaint of squinting eyes outward in both eyes since 9 years old. There was 90 PD exotropia in upgaze, 70 PD in primary gaze, 50 PD in downgaze. Bilateral IOOA grading was +3. Management in this patient was bilateral rectus lateral recession with partial hang back technique 11 mm and inferior oblique anteriorization of both eyes 1 mm posterior to inferior rectus muscle insertion. The IOOA on both eyes was eliminated post-operative, but there was 30 PD residual exotropia. The second step will be bilateral medial rectus resection. Discussion : A large V pattern with IOOA is challenging for management because it requires surgery of 2 muscles for each eye. The lateral rectus and inferior oblique muscles are close, so it was advantageous to operate simultaneously. Large exotropia requires surgery on many muscles, however operating on more than two muscles in one eye at a time can cause anterior segment ischemia. Therefore, bilateral medial rectus resection for residual exotropia will be done at different times. Conclusion : Large V pattern exotropia with inferior oblique overaction is a challenging case to manage. Due to its complex nature, it is advantageous to operate adjacent muscles.